PENDEKATAN PEMBINA EKSTRAKURIKULER DALAM MEMBENTUK KOMPETENSI SISWA DI MADRASAH ALIYAH TAHFIDZIL QUR'AN YAYASAN ISLAMIC CENTRE SUMATERA UTARA - Zahara Salma; Husnul Mardiyah Daulay; Ihsanatantri; Ahmad Zaki (STKIP Subang, 2026)
Extracurricular activities are one of the educational facilities that play an important role in developing students’ competencies beyond formal learning. This study aims to identify the approaches used by extracurricular supervisors in shaping students’ competencies at Madrasah Aliyah Tahfizhil Qur’an Yayasan Islamic Centre Sumatera Utara. The study employed a qualitative method with a descriptive approach. Data collection techniques were conducted through interviews with extracurricular supervisors. The findings revealed that a relaxed yet disciplined coaching approach was able to improve students’ motivation, self-confidence, and involvement in extracurricular activities. In addition, extracurricular activities contributed to developing students’ competencies such as discipline, responsibility, communication skills, teamwork, and leadership. This study also showed that an individual approach tailored to students’ characteristics is an important factor in the success of extracurricular guidance.